2015
DOI: 10.1155/2015/501471
|View full text |Cite
|
Sign up to set email alerts
|

Rice Husk Filled Polymer Composites

Abstract: Natural fibers from agricultural wastes are finding their importance in the polymer industry due to the many advantages such as their light weight, low cost and being environmentally friendly. Rice husk (RH) is a natural sheath that forms around rice grains during their growth. As a type of natural fiber obtained from agroindustrial waste, RH can be used as filler in composites materials in various polymer matrices. This review paper is aimed at highlighting previous works of RH filled polymer composites to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(88 citation statements)
references
References 58 publications
2
85
0
1
Order By: Relevance
“…The increasing awareness of and demand for greener and more sustainable materials, the soaring prices of petroleum-based plastics (Robertson et al 2013;Arjmandi et al 2015), and environmental friendliness regulations regarding recycling issues have attracted the attention of researchers in the field of composites worldwide. Because rice husk and straw are major waste products worldwide, the utilization of agricultural waste is of prime importance, second only to the utilization of industrial wastes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing awareness of and demand for greener and more sustainable materials, the soaring prices of petroleum-based plastics (Robertson et al 2013;Arjmandi et al 2015), and environmental friendliness regulations regarding recycling issues have attracted the attention of researchers in the field of composites worldwide. Because rice husk and straw are major waste products worldwide, the utilization of agricultural waste is of prime importance, second only to the utilization of industrial wastes.…”
Section: Introductionmentioning
confidence: 99%
“…The incineration of RH is strongly discouraged, as it could generate undesired byproducts such as ash, fumes, and toxic gases, causing serious air pollution. Therefore, a number of researchers have studied and reported on various applications that involve RH (Arjmandi et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The collected values at 10 and 30% wt were compared with similar samples prepared using a commercial silica and they found that the mechanical properties turned out to be higher than those observed in homologous samples. The economic analysis of the materials and the whole process (BCB preparation and silica extraction) showed that the production with a 20 wt% silica can be considered economically viable, when the energy recovered from the rice husk burning is reused [72] [91]. In addition, the collected data by thermogravimetry and mechanical analysis showed that all the formulations investigated could be used to manufacture materials for some packaging applications such as boxes, containers and crates [91].…”
Section: Rice Fibre Bio-composite Boardsmentioning
confidence: 99%
“…Nevertheless the husk, has drawn major attention to BCB panel. The husk component consists of 30%-51% Cellulose, 18.5%-25.71% hemicelluloses, 20%-25.42% lignin, 15%-17% silica, 2%-5% soluble materials and moisture content of 5%-10% [71][72][73]. Like rice straw or wheat straw, rice husk is a cellulose based fibrous materials [74] and has been proved to be useful for various applications due to its toughness, resistant to weathering, abrasiveness, unique chemical composition and high availability [75][76][77][78][79][80].…”
Section: Rice Fibre Bio-composite Boardsmentioning
confidence: 99%
“…Generally, fillers improve the physico‐mechanical properties of polymers, further reduce the cost of the material or achieve both objectives . Recently, using RH and especially rice husk ash (RHA)—which is obtained after controlled burning of RH—as fillers in the polymers, has grown rapidly because of their low cost, low density, high toughness, biodegradability, non‐hazardousness (compared to glass and carbon fibers), and above all the availability from the renewable resources . Therefore, it was thought in the current research to use the grounded RHP without burning as filler in rubber to reduce the environmental problems where there is lack of studies concerning its utilization compared to RHA, which was previously reported by many studies .…”
Section: Introductionmentioning
confidence: 99%